A method for preparing multi-layer core-shell structure modified graphite felt
By forming a multi-layer structural cladding layer of carbon/silica/silver nanowires on the surface of the graphite felt, and forming a nitrogen-doped carbon cladding layer through the reaction of polydopamine and polyquaternary ammonium salt, the problem of low conductivity and chemical activity of the graphite felt is solved, significantly improving the performance of the battery.
Patent Information
- Application Number
- CN202411102805.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-08-13
AI Technical Summary
The conductivity and chemical activity of existing graphite felt electrodes are low, which affects battery performance.
A carbon/silica/silver nanowire multi-layer structural cladding layer is formed in situ on the surface of the graphite felt, and a nitrogen-doped carbon cladding layer is formed through the reaction of polydopamine and polyquaternary ammonium salt to enhance conductivity and reaction activity.
The voltage efficiency, energy efficiency and capacity retention rate of the battery are significantly improved, and the overall performance of the electrode is improved.
Smart Images

Figure CN118645640B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of all-vanadium liquid flow battery electrodes, and in particular relates to a method for preparing a multi-layer core-shell structure modified graphite felt. Background Art
[0002] All-vanadium liquid flow batteries have become the most mature liquid flow battery technology at present due to their high safety, large energy storage scale, long charge and discharge cycle life, and recyclable electrolyte. They achieve mutual conversion of electrical energy and chemical energy through reversible redox reactions in the positive and negative vanadium ion electrolytes.
[0003] Electrodes are important materials for all-vanadium flow batteries and are the site of the redox reaction of vanadium ions. The conductivity of the electrode itself and the area of the interface between the electrode and the electrolyte are two key factors affecting battery performance. Graphite felt, as a commonly used electrode material, has excellent acid resistance. The pores inside it allow the electrolyte to flow and interact electronically with the graphite felt fibers. However, there are still problems with low conductivity and electrochemical activity, so it is necessary to modify it to improve its performance. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a method for preparing a multi-layer core-shell structure modified graphite felt, in which a carbon / silicon dioxide / silver nanowire multi-layer structure coating layer is in situ formed on the surface of the graphite felt, thereby increasing the electrical conductivity and reaction active sites and improving the battery efficiency.
[0005] The present invention adopts the following technical solution:
[0006] A method for preparing a multilayer core-shell structure modified graphite felt comprises at least the following steps:
[0007] Step S1: adding 5-10 parts by mass of graphite felt, 0.5-1.5 parts by mass of silver salt, and 3-4 parts by mass of end-capping agent to 1000 parts by mass of solvent and soaking for 12 hours, heating to 120°C and starting stirring, then adding 0.05-0.1 parts by mass of cupric chloride dihydrate, and reacting for 1 hour; after the reaction is completed, taking out the graphite felt and adding it to 200 parts by mass of isopropanol, and at the same time adding 4-6 parts by mass of ammonia water and 0.3-0.7 parts by mass of 50% aqueous dispersion of ethyl orthosilicate, stirring and reacting at 25°C for 8 hours; taking out the graphite felt, washing it with a polyquaternary ammonium salt solution, and then soaking it in a dopamine reaction prepolymer solution, heating it to 80°C and reacting for 12 hours, after the reaction is completed, taking out the graphite felt, washing it with an 80% volume concentration ethanol solution, and then drying it to obtain a composite graphite felt;
[0008] Step S2: placing the composite graphite felt in an atmosphere furnace, evacuating the furnace and then passing nitrogen, first raising the temperature to 100°C, keeping it for 1 hour, then raising the temperature to 500-800°C, keeping it for 2 hours, and the heating rate is 10°C / min. After calcination, naturally cool it to 25°C in a nitrogen atmosphere to obtain modified graphite felt.
[0009] Preferably, the silver salt in step S1 includes at least one of silver acetate and silver nitrate.
[0010] Preferably, the end-capping agent in step S1 includes at least one of polyvinyl pyrrolidone, sodium dodecyl sulfate, methacrylic acid, and polyacrylic acid.
[0011] Preferably, the polyquaternary ammonium salt in step S1 includes at least one of polytrimethylallyl ammonium chloride, polydimethyldiallyl ammonium chloride and polydiallyl dimethyl ammonium chloride.
[0012] Preferably, the polyquaternary ammonium salt solution in step S1 contains sodium chloride;
[0013] Preferably, the mass ratio of polyquaternium salt, sodium chloride and water in the polyquaternium salt solution in step S1 is 10-30:3:100.
[0014] Preferably, the solvent in step S1 includes at least one of ethylene glycol, glycerol, a glucose aqueous solution, and an ascorbic acid aqueous solution.
[0015] Preferably, the dopamine reaction prepolymer solution in step S1 is prepared as follows: 2 parts by mass of dopamine hydrochloride are added to 1000 parts by mass of a 50 mmol / L Tris-HCl buffer solution, dispersed and dissolved to obtain a dopamine reaction prepolymer solution.
[0016] The beneficial effects of the present invention include at least:
[0017] 1. The present invention in situ synthesizes a carbon / silicon dioxide / silver nanowire multilayer coating layer on the surface of graphite felt, wherein the carbon and silver nanowires can provide excellent electrical conductivity, and the silicon dioxide oxide layer can provide more redox sites, thereby improving the voltage efficiency and energy efficiency of the battery;
[0018] 2. The present invention firmly adheres the positively charged core-shell structured silver nanowires to the surface of graphite felt fibers by in-situ polymerization of polydopamine. After carbonization, the carbon layer can fix the core-shell structured silver nanowires, thereby improving the capacity retention rate of the battery.
[0019] 3. The present invention converts the potential of the silicon dioxide layer from negative to positive through cleaning with polyquaternary ammonium salt, thereby better attracting electrons for reaction, further carbonizing the polydopamine coating layer and the polyquaternary ammonium salt layer, and forming a nitrogen-doped carbon coating layer on the surface of the graphite felt. The introduction of nitrogen atoms makes the carbon coating layer have more defects and vacancies, thereby enhancing the electrochemical reaction activity and improving the voltage efficiency and energy efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of a preparation method of a multi-layer core-shell structure modified graphite felt of the present invention;
[0021] Figure 2 is a scanning electron microscope image of the modified graphite felt in Example 1 of the present invention;
[0022] Figure 3 TEM and mapping images of silver and silicon elements of the core-shell structured silver nanowires coated with silicon dioxide in Example 1 of the present invention;
[0023] Figure 4 is the nitrogen XPS narrow spectrum of the modified graphite felt in Examples 1-4 of the present invention;
[0024] Figure 5 It is a comparison chart of the resistivity of graphite felt prepared in Example 1 of the present invention and Comparative Example 4. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with specific embodiments and drawings, but the embodiments of the present invention are not limited thereto. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] See also Figure 1 , is a schematic diagram of a method for preparing a multi-layer core-shell structure modified graphite felt according to the present invention;
[0027] Step S1: adding 5-10 parts by mass of graphite felt, 0.5-1.5 parts by mass of silver salt, and 3-4 parts by mass of end-capping agent to 1000 parts by mass of solvent and soaking for 12 hours, heating to 120°C and starting stirring, then adding 0.05-0.1 parts by mass of cupric chloride dihydrate to react; after the reaction is completed, taking out the graphite felt and adding it to 200 parts by mass of isopropanol, and at the same time adding 4-6 parts by mass of ammonia water and 0.3-0.7 parts by mass of 50% aqueous dispersion of ethyl orthosilicate, stirring and reacting at 25°C for 8 hours; taking out the graphite felt, washing the graphite felt with a polyquaternary ammonium salt solution, then soaking it in a dopamine reaction prepolymer solution, heating to 80°C and reacting for 12 hours, after the reaction is completed, taking out the graphite felt, washing the graphite felt with an 80% volume concentration ethanol solution, and then drying to obtain a composite graphite felt;
[0028] Step S2: placing the composite graphite felt in an atmosphere furnace, evacuating the furnace and then passing nitrogen, first raising the temperature to 100°C, keeping it for 1 hour, then raising the temperature to 500-800°C, keeping it for 2 hours, and the heating rate is 10°C / min. After calcination, naturally cool it to 25°C in a nitrogen atmosphere to obtain modified graphite felt.
[0029] Embodiment 1:
[0030] This embodiment includes the following steps:
[0031] Step S1: 5g of graphite felt, 0.5g of silver nitrate, and 3g of polyvinyl pyrrolidone are added to 1000g of ethylene glycol and soaked for 12h, heated to 120°C and stirred, and then 0.1g of copper chloride dihydrate is added to react; after the reaction is completed, the graphite felt is taken out and added to 200g of isopropanol, and 4g of ammonia water and 0.3g of 50% by mass of ethyl orthosilicate aqueous dispersion are added at the same time, and stirred at 25°C for 8h; the graphite felt is taken out and washed with a polytrimethylallyl ammonium chloride solution, the polytrimethylallyl ammonium chloride solution contains sodium chloride, and the mass ratio of polytrimethylallyl ammonium chloride, sodium chloride and water is 10:3:100, and then immersed in a dopamine reaction prepolymer solution, heated to 80°C for reaction for 12h, after the reaction is completed, the graphite felt is taken out, and the graphite felt is washed with an 80% volume concentration ethanol solution, and then dried to obtain a composite graphite felt;
[0032] Step S2: placing the composite graphite felt in an atmosphere furnace, evacuating the furnace and then passing nitrogen, first raising the temperature to 100° C., keeping the temperature for 1 hour, then raising the temperature to 800° C., keeping the temperature for 2 hours, and the heating rate is 10° C. / min. After the calcination, naturally cooling the furnace to 25° C. in a nitrogen atmosphere to obtain a modified graphite felt;
[0033] Figure 2 (a) is a scanning electron microscope image of the modified graphite felt in this embodiment, and it can be clearly seen that there is a load on the surface of the graphite felt fiber. Figure 2 (b) is a magnified SEM image of the load, showing that carbon-coated core-shell silver nanowires are distributed in it; further, Figure 3 (a) is a TEM image of a silver core-shell structured silver nanowire. It can be seen that the outer layer of the silver nanowire is coated with silicon dioxide. Figure 3 (b) and (c) are the distribution diagrams of silver and silicon elements, respectively. The results show that the silica shell has been successfully coated on the surface of the silver nanowires to form a core-shell structure silver nanowires; after calcination, Figure 4 (a), (b), (c) and (d) are respectively the nitrogen XPS narrow spectra of the modified graphite felt in Examples 1-4, showing characteristic peaks of nitrogen, indicating that the carbon layer contains nitrogen doping.
[0034] Embodiment 2:
[0035] This embodiment includes the following steps:
[0036] Step S1: 7.5g of graphite felt, 1g of silver nitrate, and 3.8g of sodium dodecyl sulfate are added to 1000g of propylene glycol and soaked for 12h, heated to 120°C and stirred, and then 0.05g of cupric chloride dihydrate is added to react; after the reaction is completed, the graphite felt is taken out and added to 200g of isopropanol, and 5g of ammonia water and 0.5g of 50% by mass of ethyl orthosilicate aqueous dispersion are added at the same time, and stirred at 25°C for reaction for 8h; the graphite felt is taken out and washed with a polydimethyldiallyl ammonium chloride solution, the polydimethyldiallyl ammonium chloride solution contains sodium chloride, and the mass ratio of polydimethyldiallyl ammonium chloride, sodium chloride and water is 25:3:100, and then immersed in a dopamine reaction prepolymer solution, heated to 80°C for reaction for 12h, after the reaction is completed, the graphite felt is taken out, and the graphite felt is washed with an 80% volume concentration ethanol solution, and then dried to obtain a composite graphite felt;
[0037] Step S2: placing the composite graphite felt in an atmosphere furnace, evacuating the furnace and then passing nitrogen, first raising the temperature to 100°C and keeping it for 1 hour, then raising the temperature to 600°C and keeping it for 2 hours, with a heating rate of 10°C / min. After calcination, naturally cool it to 25°C in a nitrogen atmosphere to obtain modified graphite felt.
[0038] Embodiment 3:
[0039] This embodiment includes the following steps:
[0040] Step S1: 10g of graphite felt, 1.5g of silver nitrate, and 4g of methacrylic acid are added to 1000g of glucose aqueous solution and soaked for 12h, heated to 120°C and stirred, and then 0.1g of copper chloride dihydrate is added to react; after the reaction is completed, the graphite felt is taken out and added to 200g of isopropanol, and 6g of ammonia water and 0.7g of 50% by mass of ethyl orthosilicate aqueous dispersion are added at the same time, and stirred at 25°C for 8h; the graphite felt is taken out and washed with a polydiallyl dimethyl ammonium chloride solution, the polydiallyl dimethyl ammonium chloride solution contains sodium chloride, and the mass ratio of polydiallyl dimethyl ammonium chloride, sodium chloride and water is 30:3:100, and then immersed in a dopamine reaction prepolymer solution, heated to 80°C for reaction for 12h, after the reaction is completed, the graphite felt is taken out, and the graphite felt is washed with an 80% volume concentration ethanol solution, and then dried to obtain a composite graphite felt;
[0041] Step S2: placing the composite graphite felt in an atmosphere furnace, evacuating the furnace and then passing nitrogen, first raising the temperature to 100°C and keeping it for 1 hour, then raising the temperature to 700°C and keeping it for 2 hours, with a heating rate of 10°C / min. After calcination, naturally cool it to 25°C in a nitrogen atmosphere to obtain modified graphite felt.
[0042] Embodiment 4:
[0043] This embodiment includes the following steps:
[0044] Step S1: 5g of graphite felt, 1g of silver nitrate, and 3.5g of polyvinyl pyrrolidone are added to 1000g of ethylene glycol and soaked for 12h, heated to 120°C and stirred, and then 0.08g of cupric chloride dihydrate is added to react; after the reaction is completed, the graphite felt is taken out and added to 200g of isopropanol, and 4g of ammonia water and 0.7g of 50% by mass of ethyl orthosilicate aqueous dispersion are added at the same time, and stirred at 25°C for 8h; the graphite felt is taken out and washed with a polydimethyldiallylammonium chloride solution, the polydimethyldiallylammonium chloride solution contains sodium chloride, and the mass ratio of polyquaternary ammonium salt, sodium chloride and water is 30:3:100, and then immersed in a dopamine reaction prepolymer solution, heated to 80°C for reaction for 12h, after the reaction is completed, the graphite felt is taken out, and the graphite felt is washed with an 80% volume concentration ethanol solution, and then dried to obtain a composite graphite felt;
[0045] Step S2: placing the composite graphite felt in an atmosphere furnace, evacuating the furnace and then passing nitrogen, first raising the temperature to 100°C and keeping it for 1 hour, then raising the temperature to 500°C and keeping it for 2 hours, with a heating rate of 10°C / min. After calcination, naturally cool it to 25°C in a nitrogen atmosphere to obtain modified graphite felt.
[0046] Embodiment 5:
[0047] This embodiment includes the following steps:
[0048] Step S1: 5g of graphite felt, 1g of silver nitrate, and 3.5g of polyvinyl pyrrolidone are added to 1000g of ascorbic acid aqueous solution and soaked for 12h, heated to 120°C and stirred, and then 0.1g of cupric chloride dihydrate is added to react; after the reaction is completed, the graphite felt is taken out and added to 200g of isopropanol, and 4g of ammonia water and 0.7g of 50% by mass of ethyl orthosilicate aqueous dispersion are added at the same time, and stirred for reaction at 25°C for 8h; the graphite felt is taken out and washed with a polydimethyldiallylammonium chloride solution, the polydimethyldiallylammonium chloride solution contains sodium chloride, and the mass ratio of polyquaternary ammonium salt, sodium chloride and water is 20:3:100, and then immersed in a dopamine reaction prepolymer solution, heated to 80°C and reacted for 12h, after the reaction is completed, the graphite felt is taken out, and the graphite felt is washed with an 80% volume concentration ethanol solution, and then dried to obtain a composite graphite felt;
[0049] Step S2: placing the composite graphite felt in an atmosphere furnace, evacuating the furnace and then passing nitrogen, first raising the temperature to 100°C and keeping it for 1 hour, then raising the temperature to 800°C and keeping it for 2 hours, with a heating rate of 10°C / min. After calcination, naturally cool it to 25°C in a nitrogen atmosphere to obtain modified graphite felt.
[0050] Embodiment 6:
[0051] This embodiment includes the following steps:
[0052] Step S1: 5g of graphite felt, 1g of silver acetate, and 3.5g of polyvinyl pyrrolidone are added to 1000g of ethylene glycol and soaked for 12h, heated to 120°C and stirred, and then 0.1g of cupric chloride dihydrate is added to react; after the reaction is completed, the graphite felt is taken out and added to 200g of isopropanol, and 5g of ammonia water and 0.5g of 50% by mass of ethyl orthosilicate aqueous dispersion are added at the same time, and stirred at 25°C for 8h; the graphite felt is taken out and washed with a polydimethyldiallylammonium chloride solution, the polydimethyldiallylammonium chloride solution contains sodium chloride, and the mass ratio of polyquaternary ammonium salt, sodium chloride and water is 20:3:100, and then immersed in a dopamine reaction prepolymer solution, heated to 80°C for reaction for 12h, after the reaction is completed, the graphite felt is taken out, and the graphite felt is washed with an 80% volume concentration ethanol solution, and then dried to obtain a composite graphite felt;
[0053] Step S2: placing the composite graphite felt in an atmosphere furnace, evacuating the furnace and then passing nitrogen, first raising the temperature to 100°C and keeping it for 1 hour, then raising the temperature to 800°C and keeping it for 2 hours, with a heating rate of 10°C / min. After calcination, naturally cool it to 25°C in a nitrogen atmosphere to obtain modified graphite felt.
[0054] Comparative Example 1
[0055] This comparative example comprises the following steps:
[0056] Step S1: 5 g of graphite felt, 0.5 g of silver nitrate, and 3 g of polyvinyl pyrrolidone are added to 1000 g of ethylene glycol and soaked for 12 h, heated to 120 ° C and stirred, and then 0.1 g of copper chloride dihydrate is added to react; after the reaction is completed, the graphite felt is taken out and soaked in a dopamine reaction prepolymer solution, heated to 80 ° C and reacted for 12 h, after the reaction is completed, the graphite felt is taken out, and the graphite felt is cleaned with an 80% volume concentration ethanol solution, and then dried to obtain a composite graphite felt;
[0057] Step S2: placing the composite graphite felt in an atmosphere furnace, evacuating the furnace and then passing nitrogen, first raising the temperature to 100°C and keeping it for 1 hour, then raising the temperature to 800°C and keeping it for 2 hours, with a heating rate of 10°C / min. After calcination, naturally cool it to 25°C in a nitrogen atmosphere to obtain modified graphite felt.
[0058] Comparative Example 2
[0059] This comparative example comprises the following steps:
[0060] Step S1: 5g of graphite felt, 0.5g of silver nitrate, and 3g of polyvinyl pyrrolidone are added to 1000g of ethylene glycol and soaked for 12h, heated to 120°C and stirred, and then 0.1g of copper chloride dihydrate is added to react; after the reaction is completed, the graphite felt is taken out and added to 200g of isopropanol, and 4g of ammonia water and 0.3g of 50% by mass of ethyl orthosilicate aqueous dispersion are added at the same time, and the reaction is stirred at 25°C for 8h; the graphite felt is taken out and cleaned with a polytrimethylallyl ammonium chloride solution, the polytrimethylallyl ammonium chloride solution contains sodium chloride, and the mass ratio of polytrimethylallyl ammonium chloride, sodium chloride and water is 10:3:100, and then dried to obtain a composite graphite felt;
[0061] Step S2: placing the composite graphite felt in an atmosphere furnace, evacuating the furnace and then passing nitrogen, first raising the temperature to 100°C and keeping it for 1 hour, then raising the temperature to 800°C and keeping it for 2 hours, with a heating rate of 10°C / min. After calcination, naturally cool it to 25°C in a nitrogen atmosphere to obtain modified graphite felt.
[0062] Comparative Example 3:
[0063] This comparative example comprises the following steps:
[0064] 5g of graphite felt, 0.5g of silver nitrate and 3g of polyvinyl pyrrolidone were added to 1000g of ethylene glycol and soaked for 12h, heated to 120℃ and stirred, and then 0.1g of cupric chloride dihydrate was added to react; after the reaction was completed, the graphite felt was taken out and added to 200g of isopropanol, and 4g of ammonia water and 0.3g of 50% by mass aqueous dispersion of ethyl orthosilicate were added at the same time, and stirred for reaction at 25℃ for 8h; the graphite felt was taken out and washed with polytrimethylallyl ammonium chloride solution, which contained sodium chloride, and the mass ratio of polytrimethylallyl ammonium chloride, sodium chloride and water was 10:3:100, and then soaked in dopamine reaction prepolymer solution, heated to 80℃ and reacted for 12h, and after the reaction was completed, the graphite felt was taken out and washed with 80% volume concentration ethanol solution, and then dried to obtain modified graphite felt.
[0065] Comparative Example 4
[0066] Blank graphite felt.
[0067] Resistivity test method: The test was performed using a Suzhou Jingge Electronics ST2258C digital four-probe tester. The graphite felt was cut into a size of 10 cm×5 cm. The resistivity test was performed on 9 fixed positions. The resistivity of Comparative Example 4 and Example 1 was obtained by taking the average value.
[0068] Battery test method: The multilayer core-shell structure modified graphite felt obtained in Examples 1-6 and Comparative Examples 1-4 were assembled into a battery stack, and the battery charge and discharge performance test was performed under the same operating conditions, and the coulomb efficiency, voltage efficiency and energy efficiency were recorded. The test results are shown in Table 1:
[0069] Table 1 Battery performance test table of battery stacks assembled using graphite felt from examples and comparative examples
[0070]
[0071] As can be seen from Table 1, compared with Comparative Example 4, Examples 1-6 and Comparative Example 1-2 have higher voltage efficiency and energy efficiency. In addition, Figure 5Comparing the resistivity of the graphite felt prepared in Example 1 and Comparative Example 4, it can also be seen that the resistivity of the graphite felt prepared in this example is significantly lower than that of the blank graphite felt, indicating that the conductivity of the graphite felt can be significantly improved by the method of the present invention. This is mainly because the modified graphite felt prepared in the present invention contains a three-layer hybrid layer of carbon / silicon dioxide / silver nanowires, in which the carbon and silver nanowires can provide excellent conductivity, and the silicon dioxide oxide layer can provide more redox sites, thereby improving the voltage efficiency and energy efficiency of the battery; compared with Comparative Example 3, Examples 1-6, Comparative Examples 1-2 and Comparative Example 4 have higher voltage efficiency and energy efficiency, mainly because the heat treatment process of step S2 is not performed during the preparation process of Comparative Example 3. The present invention uses a polydopamine coating layer to modify the graphite felt. During the coating process, low-conductivity polydopamine is attached to the graphite felt fibers without high-temperature calcination treatment. It will block the electrolyte transmission channel, causing the battery voltage efficiency and energy efficiency to be significantly reduced; compared with Comparative Example 2, Examples 1-6, Comparative Example 1 and Comparative Example 3 have a higher capacity retention rate after 100 cycles, mainly because there is no dopamine carbon layer in the preparation process of Comparative Example 2. Although the silver nanowire has excellent conductivity, due to the lack of a coating layer to provide adhesion, the silver nanowire only relies on physical entanglement to modify the graphite felt, which is easily washed by the electrolyte, indicating that the present invention uses the method of in-situ polymerization of polydopamine to firmly adhere the core-shell structure silver nanowire to the surface of the graphite felt fiber. After carbonization, the carbon layer can fix the core-shell structure silver nanowire and improve the capacity retention rate of the battery. In addition, the carbonized polydopamine coating layer and the polyquaternary ammonium salt layer can form a nitrogen-doped carbon coating layer on the surface of the graphite felt. The introduction of nitrogen atoms makes the carbon coating layer have more defects and vacancies, improves the electrochemical reaction activity, and improves the voltage efficiency and energy efficiency of the battery. Compared with Comparative Example 1, Examples 1-6 have higher voltage efficiency and energy efficiency, mainly because no silicon dioxide oxide layer is formed during the preparation process of Comparative Example 1, and the silicon dioxide oxide layer can provide more redox sites. At the same time, through the cleaning of polyquaternary ammonium salt, the potential of the silicon dioxide layer is converted from negative to positive, which better attracts electrons for reaction, thereby improving the voltage efficiency and energy efficiency of the battery.
[0072] From the above detailed description of the embodiments of the present invention, it can be understood that the present invention provides a method for preparing a multi-layer core-shell structure modified graphite felt. By synthesizing a carbon / silicon dioxide / silver nanowire coating layer, the core-shell structure silver nanowires are better adhered to the graphite felt fibers. In addition, more conductive networks and redox sites are introduced to increase the voltage efficiency, energy efficiency and capacity retention rate of the all-vanadium liquid flow battery.
[0073] Although the preferred implementation of the present invention has been disclosed as above, it does not limit the present invention. Any technician in this field can make appropriate improvements without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the scope defined by the claims.
Claims
1. A method for preparing a multilayer core-shell structure modified graphite felt, characterized in that: At least the following steps are included: Step S1: 5-10 parts by mass of graphite felt, 0.5-1.5 parts by mass of silver salt, and 3-4 parts by mass of end-capping agent are added to 1000 parts by mass of solvent and soaked for 12 hours, heated to 120°C and stirred, and then 0.05-0.1 parts by mass of cupric chloride dihydrate are added and reacted for 1 hour; after the reaction is completed, the graphite felt is taken out and added to 200 parts by mass of isopropanol, and 4-6 parts by mass of ammonia water and 0.3-0.7 parts by mass of 50% aqueous dispersion of ethyl orthosilicate are added at the same time, and stirred for reaction at 25°C for 8 hours; the graphite felt is taken out, washed with a polyquaternary ammonium salt solution, and then immersed in a dopamine reaction prepolymer solution, heated to 80°C and reacted for 12 hours, and after the reaction is completed, the graphite felt is taken out and washed with an ethanol solution with a volume concentration of 80%, and then dried to obtain a composite graphite felt; the polyquaternary ammonium salt includes at least one of polytrimethylallyl ammonium chloride, polydimethyldiallyl ammonium chloride, and polydiallyl dimethyl ammonium chloride; Step S2: placing the composite graphite felt in an atmosphere furnace, evacuating the furnace and then passing nitrogen, first raising the temperature to 100°C, keeping it warm for 1 hour, then raising the temperature to 500-800°C, keeping it warm for 2 hours, and the heating rate is 10°C / min. After calcination, naturally cool it to 25°C in a nitrogen atmosphere to obtain the modified graphite felt.
2. The method for preparing a multi-layer core-shell structure modified graphite felt according to claim 1, characterized in that: In step S1, the silver salt includes at least one of silver acetate and silver nitrate.
3. The method for preparing a multi-layer core-shell structure modified graphite felt according to claim 1, characterized in that: In step S1, the end-capping agent includes at least one of polyvinyl pyrrolidone, sodium dodecyl sulfate, and polyacrylic acid.
4. The method for preparing a multi-layer core-shell structure modified graphite felt according to claim 1, characterized in that: The polyquaternary ammonium salt solution in step S1 also contains sodium chloride.
5. The method for preparing a multi-layer core-shell structure modified graphite felt according to claim 1, characterized in that: The mass ratio of polyquaternium salt, sodium chloride and water in the polyquaternium salt solution is 10-30:3:
100.
6. The method for preparing a multi-layer core-shell structure modified graphite felt according to claim 1, characterized in that: In step S1, the solvent includes at least one of ethylene glycol, glycerol, a glucose aqueous solution, and an ascorbic acid aqueous solution.
7. The method for preparing a multi-layer core-shell structure modified graphite felt according to claim 1, characterized in that: In the step S1, the dopamine reaction prepolymer solution is prepared as follows: 2 parts by mass of dopamine hydrochloride are added to 1000 parts by mass of a Tris-HCl buffer solution with a concentration of 50 mmol / L, and dispersed and dissolved to obtain the dopamine reaction prepolymer solution.
Citation Information
Patent Citations
Electrode and application of electrode as negative electrode in all-vanadium redox flow battery
CN114497580A
Electrochemical modification method of vanadium battery electrode based on silane hydrolysate
CN114824314A
Cited By
Wave-absorbing core-shell structure super-surface composite material for unmanned aerial vehicle and preparation method thereof
CN120757395A